Postmodern Public Administration. - Miller, Hugh T. (M.E. Sharpe, Inc., 2006)
Provides a counterbalance to the standard assessment-measurement-accountability prescriptions that have made showing you did your job more important than actually doing it. This work articulates a postmodern theory of public administration that challenges the field to redirect its attention away from narrow, technique-oriented scientism.